Preliminary Screening of Glycoprotein Profiles in Human Normal and Lung Cancer Sera by Different Staining Methods - Hongsachart P. (2014)
In this study, the purposes were to compare the staining methods for detection of glycoprotein profiles in normal and lung cancer serum samples and to preliminary screen the carbohydrate specificity of glycoproteins in both serum samples. Using the sequential staining methods of Pro-Q Emerald 488 glycoprotein gel staining, SYPRO® Ruby staining and silver staining revealed that the Emerald 488 glycoprotein gel staining has the specific detection of glycoproteins compared with SYPRO® Ruby and silver staining and provided the differential glycoprotein profiles between normal and lung cancer serum samples. In addition, seven FITC-labeled lectins; Con A, PNA, ECL, WGA, MAL 1, AAL and UEA, were used to detect the differentially expressed glycoproteins and the carbohydrate specificity of glycoproteins in both samples. The results of lectin staining showed that Con A, WGA and AAL lectins have the strong reactivity to the glycoproteins in both samples compared with other lectins and gave the differentially expressed glycoproteins in lung cancer sera. It indicated that the serum glycoproteins in both samples contain the high contents of mannose, GlcNAc, sialic acid and fucose (α1-3/4, a1-6) residues, in which their expression levels may be correlated to the lung cancer development. Therefore, this preliminary detection method was not only used to screen the altered glycoproteins in human normal and lung cancer sera, but also provided the different carbohydrate specificities of glycoproteins that are very useful for further selective glycoprotein purification and analysis.